2019
DOI: 10.1007/s00204-019-02425-6
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol inhibits the expression of trefoil factors (TFF) by intestinal human and porcine goblet cells

Abstract: Trefoil factors (TFFs) are bioactive peptides expressed by several epithelia, including the intestine, where they regulate key functions such as tissue regeneration, barrier function and inflammation. Although food-associated mycotoxins, including deoxynivalenol (DON), are known to impact many intestinal functions, modulation of TFFs during mycotoxicosis has never been investigated. Here, we analyzed the effect of DON on TFFs expression using both human goblet cells (HT29-16E cells) and porcine intestinal expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…However, the study on the goblet cells induced by DON was less studied. Limited results indicated that the number of goblet cells in villi and crypts decreased significantly after DON was added in vitro and in vivo [36,37]. The results from this study proved that the number of goblet cells increased significantly, especially at the higher dose.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the study on the goblet cells induced by DON was less studied. Limited results indicated that the number of goblet cells in villi and crypts decreased significantly after DON was added in vitro and in vivo [36,37]. The results from this study proved that the number of goblet cells increased significantly, especially at the higher dose.…”
Section: Discussionmentioning
confidence: 61%
“…The goblet cells not only produce mucoprotein, but also secrete some factors which can make epithelial renewed and repaired [36]. However, the study on the goblet cells induced by DON was less studied.…”
Section: Discussionmentioning
confidence: 99%
“…The intestine is the initial line of defense against food contaminants and the primary target for DON [3]. A recent study has demonstrated that DON intoxicated intestinal health by depressing the expression of trefoil factors (TFFs) in goblet cells [4]. DON induced inhibition of TFFs contributes to impaired intestinal integrity through alteration of mucosal regeneration or repair [4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has demonstrated that DON intoxicated intestinal health by depressing the expression of trefoil factors (TFFs) in goblet cells [4]. DON induced inhibition of TFFs contributes to impaired intestinal integrity through alteration of mucosal regeneration or repair [4]. Trefoil factors (TFF1, 2, and 3) are a family of protease-resistant peptides that are abundantly secreted onto the surface of the intestine by mucin-producing cells.…”
Section: Introductionmentioning
confidence: 99%
“…TFF3 protects and repairs the gastrointestinal mucosa, maintains the tight junction barrier integrity and restores normal intestinal permeability during inflammatory bowel disease pathogenesis (7). TFF3 is also present in the neural lobe of the porcine pituitary gland (8,9).…”
Section: Introductionmentioning
confidence: 99%